2001
DOI: 10.1080/17450390109381984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding regime on the metabolism of ochratoxin a during thein vitroincubation in buffered rumen fluid from cows

Abstract: Pure ochratoxin A (OA) was added to buffered rumen fluid collected from two fistulated cows and incubated under anaerobic conditions. Both animals were fed six diets containing grass, grass silage or hay, and two different amounts of concentrate consisting of barley and soybean meal. Four incubations per animal and diet were carried out at consecutive days. The concentration of OA declined exponentially to a very low or non-detectable level under all conditions examined, with half-lives at 0.51 to 2.76 h. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…This assumption is consistent with results of several in vitro studies with ochratoxin A (Müller et al, 1998(Müller et al, , 2001Özpinar et al, 1999). Müller et al (2001) added pure ochratoxin A to rumen fluid from cows which were fed six diets containing grass, grass silage or hay and two different amounts of concentrate consisting of barley and soyabean meal. The authors observed a disappearance of ochratoxin A accompanied by an appearance of ochratoxin α in the rumen fluid by replacing grass silage or hay by fresh grass and by increasing the level of concentrate in the total diet.…”
Section: Ration Compositionsupporting
confidence: 75%
“…This assumption is consistent with results of several in vitro studies with ochratoxin A (Müller et al, 1998(Müller et al, , 2001Özpinar et al, 1999). Müller et al (2001) added pure ochratoxin A to rumen fluid from cows which were fed six diets containing grass, grass silage or hay and two different amounts of concentrate consisting of barley and soyabean meal. The authors observed a disappearance of ochratoxin A accompanied by an appearance of ochratoxin α in the rumen fluid by replacing grass silage or hay by fresh grass and by increasing the level of concentrate in the total diet.…”
Section: Ration Compositionsupporting
confidence: 75%
“…Such effective deactivation explains the high tolerance of ruminants to OTA exposure (Hult and others ; Fink‐Gremmels ). Sometimes, small amounts of OTA may be found in milk that can be due to a protein‐rich diet that drastically affects the cleavage capacity by rumen microorganisms (Breitholtz‐Emanuelsson and others ; Muller and others ; Fink‐Gremmels ).…”
Section: Otamentioning
confidence: 99%
“…This effective deactivation explains the high comparable high tolerance of ruminants to ochratoxin A exposure (Hult et al 1976;Pettersson et al 1982). Drastic changes in the feed composition, and a high percentage of protein-rich concentrates in the daily diet modify, however, the cleavage capacity of rumen microorganisms (Xiao et al 1991;Muller et al 2001), which explains why incidentally small amounts of ochratoxin A could be detected in milk (Skaug 1999).…”
Section: Conversion Of Mycotoxins By the Rumen Floramentioning
confidence: 99%